AB0628 Infections in hospitalised patients with systemic lupus erythematosus- a prospective observational study from a tertiary care centre in southern india. (12th June 2018) - Alur, S.; Thabah, M.M.; Negi, V.S.; Sistla, S.
Abstract : Background: Infections are one of the main causes of morbidity and mortality in SLE. 1 The high prevalence of infection is attributed to use of immunosuppressive agents and disease activity. There is paucity of literature from India on infections, types of infections, predictors and outcome. Objectives: To determine the frequency, types and determinants of major infections in hospitalised patients with SLE. Methods: Patients with SLE (2012 SLICC-ACR criteria) aged ≥13 years, admitted to Clinical Immunology and Medicine wards were included. Clinical evaluation for major organ involvement of SLE, disease activity was assessed by SLEDAI-2K. Whenever there was a suspicion of infection appropriate work up to find the etiology of infections was done. Major infection was defined as presence of either one of the following a) sepsis b) pneumonia, or pyelonephritis, or endocarditis, or meningitis. c) skin or soft tissue infection requiring hospital admission for treatment d) Infection requiring IV antibiotic therapy. The diagnosis of infection was made by compatible clinical, microbiological and imaging criteria. Results: From December 2016 till January 2018, 63 (55 women and 8 men) were included; Mean age was 28.8±9.8 years; mean SLEDAI-2K was 14.6±7.03. Median duration of hospital stay was 14 days; range 2–64 days. Disease manifestation (including present and ever present) were arthralgia/arthritis in 51 (81%), oral ulcers 56 (88.9%), myositis 10 (15.9%), lupus nephritis 35 (55.6%), CNS lupus 14 (22.2%), serositis 14 (22.2%), cardiac involvement 13 (20.6%), APS 3 (4.8%). At the time of enrollment thrombocytopenia was present in 13 (20.6%), and leukopenia 11 (17.5%). Twenty-three of 63 (36.5%) had infections (table 1), 14/23 (60.8) were microbiologically proven, remaining (39.2%) were confrrmed by compatible clinical features and imaging. Seven of 63 (11.1%) died; 5 (21.7%) in the infection group versus 2 (5%) in no infection group, p=0.08 OR 5.58 [CI 0.98–31.7]. Thirty-four of 63 (54%) had fever on admission; 17/23 (74%) patients with infection had fever compared to 17/40 (42.5%) in no infection group, p=0.02 [OR=3.8, CI 1.2–11.7]. There was no association of lupus nephritis, CNS lupus, leukopenia, receipt of cyclophosphamide, rituximab, methylprednisolone pulse therapy with occurrence of infection. Conclusions: Almost 36% of SLE patients in hospital have infections. There appeared to be an increase in number of deaths among patients with infections. There was no association of infections with the dose of prednisolone or previous immunosuppression with cyclophosphamide. Reference: [1] Shyam C, Malaviya AN. Infection-related morbidity in systemic lupus erythematosus: a clinico-epidemiological study from northern India. Rheumatol Int. 1996; 16: 1–3. Disclosure of Interest: None declared